Peningkatan Kompetensi Guru dalam Proses Pembelajaran Melalui Supervisi Klinis di SMP Negeri 6 Mataram - Azizudin Azizudin (Universitas Pendidikan Mandalika, 2022)
This research was carried out with the objectives: 1) to improve the ability of teachers in implementing learning from designing, implementing, to evaluating, 2) to determine the frequency level of implementation of clinical supervision by school principals, and 3) the availability of quality supervision documents. This research method uses school action research which is carried out in two cycles consisting of Planning, Implementation, Observation, and Reflection. The subjects in the study were 60 teachers at SMP Negeri 6 Mataram. This research instrument uses observation sheets, interviews, and documentation. The data analysis technique uses descriptive analysis. The results of this study indicate that clinical supervision can improve teacher competence in the learning process at SMP Negeri 6 Mataram. Based on the results of data analysis of clinical supervision results, it can be concluded that; 1) of 60 teachers who obtained a minimum of Good as many as 49 people (81.67%), 2) of 60 teachers 100% of teachers were supervised, and 3) Schools had quality documents in the form of supervision programs, supervision reports, and follow-up programs.